Resource conservation program in terms of Vostokgazprom environmental policy; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Tsibulnikova M. R. Margarita Radievna; Nadyumov S. V.; Adam A. M.; Korotchenko T. V. Tatiana Valerievna (Geoecology and Environmental Protection, 2016)
Title screen